Presenting native-like HIV-1 envelope trimers on ferritin nanoparticles improves their immunogenicity - Sliepen, Kwinten (Retrovirology, 2015)
BACKGROUND: Presenting vaccine antigens in particulate form can improve their immunogenicity by enhancing B cell activation. FINDINGS: We describe ferritin-based protein nanoparticles that display multiple copies of native-like HIV-1 envelope glycoprotein trimers (BG505 SOSIP.664). Trimer-bearing nanoparticles were significantly more immunogenic than trimers in both mice and rabbits. Furthermore, rabbits immunized with the trimer-bearing nanoparticles induced significantly higher neutralizing antibody responses against most tier 1A viruses, and higher responses (but not significantly), to several tier 1B viruses and the autologous tier 2 virus than when the same trimers were delivered as soluble proteins. CONCLUSIONS: This or other nanoparticle designs may be practical ways to improve the immunogenicity of envelope glycoprotein trimers.